Bohaterowie polskiego kina - Grażyna Stachówna (Postscriptum Polonistyczne, 2020)
In her book Lords of Imagination: Lead Characters in Polish Film, from which we quote extensive fragments, the author refers to the screen protagonists who live on in our imagination. The author shows how they embody viewers’ dreams, desires and hopes. In successive chapters, the lineage of characters and hilarious anecdotes about characters and actors can be found. For this issue we reprinted fragments concerning Maciek Chełmicki (Diamond and Ashes), Andrzej Kmicic (Deluge), Henryk Kwinto (Vabank and Vabank II), and Franz Mauer (Dogs and Dogs II).